Ocupação, conflitos e conquistas : a luta pelo direito a terra para moradia e a formação do bairro de Itaúna I/Parintins-Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The research presented here addresses issues related to the land rights dispute, considering that these have always been debated throughout history, but even when it comes to revisited themes, it still integrates concerns of contemporary society. Considering what was exposed due to Amazonian territorialities, and dealing specifically with the municipality of Parintins, 367 km from the capital Manaus, east of the state, on the border with Pará, until 1991 there were large concentrations of land. They were generated from socioeconomic conjunctures that date back to the military governments of the country (1964-1985). The analysis was intended to understand the circumstances in which a group of people, until the moment of the event studied, considered to be of no social, economic or political relevance, was able to generate an alternative project to achieve the aspiration common to most Brazilian families , the right to housing. The methodological method chosen to support the collection of data and analyzes of this study was Oral History, since this methodology can be used in different disciplines of the human sciences in which one intends to work with categories such as biography, oral tradition, memories and spoken language, through qualitative research (ALBERTI, 2013). This research aimed at counting the first land occupation of the Itaúna Farm area, in Parintins, from the view of the subjects participating in the movement, using them as a source for collecting the necessary information, information that would certainly not be known through other types from sources. The use of Oral History allows us to construct a story based on the perceptions and experiences of the underprivileged classes of society, which are generally invisible within official documentations (THOMPSON, 2002).
Keywords: Movimentos sociais; Ocupação de terra; Moradia; História Oral; CIÊNCIAS HUMANAS